Improving the Activities and Learning Outcomes of Financial Accounting Through the Application of Model Numbered Heads Together - Nurmiati, Nurmiati (Universitas Negeri Makassar, 2022)
Numbered Heads Together (NHT) is one of the new learning methods that is effectively applied in schools, where this model can train and motivate students in following the teaching and learning process in the classroom. T The design of this study is class action research (PTK). The purpose of this study is to find out an overview of the application of the Numbered Heads Together (NHT) model so that it can improve the activities and learning outcomes of Financial Accounting class XI AKL 1 SMK Negeri 2 Palu for the 2021/2022 Academic Year. The research design follows the Kemmis & Mc Taggart model. This study uses 2 cycles and each cycle consists of 4 stages, namely: Planning, Implementation, Observation, and Reflection. Of the 30 students in cycle I, the criteria for Active participated in learning as many as 18 people (60%), Moderately Active 8 people (26.67%), Inactive as many as 4 people (13.33%). Based on the test results and observation results that have been carried out, this PTK only reaches cycle II because the criteria for individual absorption of 70 and classical completion of at least 85% have been achieved, namely 93.33%. The average teacher's teaching and learning activities have been